2017
DOI: 10.1007/s10649-017-9781-4
|View full text |Cite
|
Sign up to set email alerts
|

Power and identity in immigrant parents’ involvement in early years mathematics learning

Abstract: This study examined immigrant parents' involvement in early years mathematics learning, focusing on learning of multiplication in in-and out-of-school settings. Ethnographic interviews and workshops were conducted in an urban city in Japan, to examine out-of-school practices of immigrant families. Drawing from sociocultural theory of learning and the concept of appropriation (Wertsch, 1998), the role of power and identity was examined in relation to children's appropriation of an informal multiplication method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 26 publications
1
23
1
Order By: Relevance
“…Fathers with higher education level also commonly invest their time to have a discussion with their children regarding what the children do and the problem they face during their day at school. This, according to Takeuchi (2018), can positively motivates students to achieve better at school. This father's indirect involvement potentially brings stronger influence toward students' mathematics achievement compared to father's direct involvement such as helping children to solve some mathematical problems (Cao et al, 2006).…”
Section: Figure 2 the Differences Of Average In Mathematics Achievemmentioning
confidence: 99%
See 1 more Smart Citation
“…Fathers with higher education level also commonly invest their time to have a discussion with their children regarding what the children do and the problem they face during their day at school. This, according to Takeuchi (2018), can positively motivates students to achieve better at school. This father's indirect involvement potentially brings stronger influence toward students' mathematics achievement compared to father's direct involvement such as helping children to solve some mathematical problems (Cao et al, 2006).…”
Section: Figure 2 the Differences Of Average In Mathematics Achievemmentioning
confidence: 99%
“…Parents who want to be engaged and often discuss about the subject matters with their children commonly have the knowledge related to the material being discussed Takeuchi (2018). In addition, the frequency of discussion about subject matters other matters between the parents and the children indicates the harmonious communication within the family.…”
Section: The Interaction Of Parental Involvement and Parents' Educatimentioning
confidence: 99%
“…More specifically, the students' family crucially affects their interaction with school mathematics, through the students' everyday homework and through the family's broader beliefs, attitudes, emotions and practices about mathematics as experienced in everyday mathematically related (implicitly or explicitly) activities. Moreover, research evidence has shown that the ways through which a person develops his or her 2 / 18 http://www.iejme.com mathematical competence in different social practices (for example, in school or in family daily life) are usually characterized by discontinuity and the students' school mathematical practice does not imply their performing in out of school relevant practices, especially for groups not belonging to the dominant social group, such as immigrant groups (Abreu, Gorgorio, & Boistrup, 2018;Takeuchi, 2018). On the other hand, some researchers have mentioned that such discontinuities should not be viewed as obstacles, but as a variety of practices that the students can negotiate in participating in classroom activities (Hodge & Cobb, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This because of the vocabulary used in the specific research paradigm. For instance, research has been conducted within the field of bilingualism and mathematics (e.g., Domínguez, 2011;Planas, 2014;Takeuchi, 2018) and even though the notion of inclusion is not used, the studies aim to create opportunities to include bilingual students. Another example is research with low-achieving students (Ben-David Kolikant & Broza, 2011) with the aim of promoting learning.…”
Section: Discussionmentioning
confidence: 99%